Proporsi peresepan probiotik pada gastroenteritis akut pasien pediatri di bangsal rawat inap RS X pada Februari 2015 - Virginia, Dita Maria (Pharmaciana, 2016)
Pediatric patients are one of the target groups of the National Health System in Indonesia that requires special attention in therapy because their anatomy physiology was immature. A lot of probiotics indicated for acute gastroenteritis (AGE) for pediatric patients. Probiotic prescribing includes the types of probiotic, dosage and duration for AGE has not been discussed clearly. The aim of our study was to determine the proportion of probiotic that have prescribed for acute gastroenteritis topediatric agedin hospitalized. This study was analytical observational with cross sectional design. Data was obtained retrospectively with non-purposive sampling.Samplesize was based on cross-sectional design calculation and obtained a number of 200 medical records from Hospital X, IndonesiaonFebruary 2015. This study used secondary data from medical records. Data collected was patient identity, patientaged, probiotic prescribing includes the types of probiotic, dosage and duration. Data have been analyzed in descriptive and Mann-Whitney to observe the difference between types of probiotic, dosage and duration probiotic used topediatric aged. This study showed this hospital only used 5 probiotic brands. Group aged <2 years is more used of 3 types of probiotic species while at the age of> 2 years is prefer to use 6 types. The mean dose of probiotic is greater in the group aged >2 years. Probiotic duration in the group <2 years is for 4 days while in those aged >2 years in duration 5 days. The number of cases that do not fit with the recommended dose packs is more commonly found at age <2 years. There is a different proportion between type of probiotic (p=0.000), dose of probiotic (p=0.040), and probiotic duration (p=0.008) with pediatric aged. There was a statistically significant difference between types of probiotic, dosage and duration probiotic used to pediatric aged.